Introdução - A doença feminina - Showalter, Elaine; Salvi, Ana Carolina (Tempos Históricos, 2024)
Texto originalmente publicado em: SHOWALTER, Elaine. Introduction. The female malady. In: The Female Malady: Women, Madness and English Culture, 1830 to 1980. Mishawaka: Knopf Doubleday Publishing Group, 1985.